PEMANFAATAN MEDIA SOSIAL YOUTUBE SEBAGAI SARANA PEMBELAJARAN SIRAH NABAWIYAH SERTA PENGARUHNYA TERHADAP HASIL BELAJAR SISWA SMP ALWAFI ISLAMIC BOARDING SCHOOL - Sulhan Hadi; Oking Setia Priyatna; Salati Asmahasanah (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the low understanding of Al Wafi IBS students on the Sirah Nabawiyyah subject. The purposes of this study were: (1) to determine the use of social media Yutube as a means of learning siroh nabawiyah, and (2) to determine learning outcomes before and after the implementation of the use of youtube social media on student learning outcomes. The method in this study uses descriptive quantitative methods, as well as how to collect data used are interviews, observation, and recording. Analyzing data using data reduction methods, presenting data, and making conclusions. The results of the study show that: (1) there is a significant effect between the use of YouTube social media on the learning outcomes of the seventh grade students of Sirah Nabawiyyah at Al Wafi IBS. The magnitude of the effect is 42.3%, and (2) the use of students' YouTube social media can be said to be moderate (good). This is obtained from the results of student questionnaires with details of 78.6% Keywords: Youtube Social Media, Sirah Nabawiyyah Learning Outcomes